HUBUNGAN DUKUNGAN KELUARGA DENGAN TINGKAT STRESS PENDERITA TB PARU - Kristina Murniati Sihombing; Siti Rahmalia Hirani D; Rismadefi " Woferst (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
Abstract Family support is one way to lower the stress level, especially with pulmonary tuberculosis. This study aims to determine the relationship of family support with the stress levels of pulmonary tuberculosis patients. This study aims to determine the relation of family support with level of stress  on TB pulmonary patients. This design of the research is descriptive correlation with cross sectional approach.The total sample is 47 respondents were taken based on inclusion and exclusion criteria using a purposive sampling. The data was coledted by using  a questionnaire that consist of two parts of family support and stress level. The data was analised by using univariate analysis to determine the frequency distribution and bivariate analysis to determine the stress level of the dependent variable. The results showed that there is a significant correlation (p value = 0.014 <0.05) that means Ho rejected or there is a significant relationship between family stress levels dukngan pulmonary tuberculosis patients. The result is expected to be a reference for health centers in providing information about anxiety and can be used as evidence based practice in the development of science to cope stress levels in TB pulmonary patients. Keywords       :    Family support, Pulmonary TB, Stress